Term limits: do they really affect fiscal policy choices? - Chiara Dalle Nogare; Roberto Ricciuti (Center for Economic Studies and ifo Institute (CESifo), 2008)
According to reputational models of political economy, a term limit may change the behavior of a chief executive because he does not have to stand for election. We test this hypothesis in a sample of 52 countries over the period 1977-2000, using government spending, social and welfare spending and deficit as policy choice variables using panel data estimation techniques. We are unable to find significant differences in the behavior of term-limited and non term-limited chief executives. This is in contrast with some previous empirical results based on U.S. states and international data.
Keywords: E62; H11; 330; term limits; comparative politics; fiscal policy; Finanzpolitik; Regelgebundene Politik; Öffentliche Schulden; Systemvergleich; Schätzung; USA; Welt